Pelatihan Pemanfaatan Limbah Rumah Tangga untuk Penanaman Sayuran dan Mikroorganisme Lokal (Mol) sebagai Ketahanan Pangan Keluarga - Rini, Aditya; Anis Widyastuti; Devi Laely Wahyu Utami; Eryna Yulianaristin; Ilham Esa Tiffani; Mala Mazida; Nofia Sholihatuzzahroh; Rida Khoirin Nisa; Siti Ita Rahmawati; Vika Lailatul Izzah; Agnita Siska Pramasdyahsari (Journal of Social Empowerment, 2024)
The aim of this community service is to encourage people to use household waste to plant vegetables and local microorganisms for food security for families and communities and to make planting media in the form of pots. The method of service is the community service method. The approach to implementing this service is asset or resource-based community empowerment. Data collection techniques use documentation, questionnaires and focus group discussions. Data analysis in this service is qualitative descriptive data analysis. The result of this service is that activities are carried out in three stages, namely the first is socialization related to the use of unused materials to make something useful, namely socialization on the manufacture and use of local microorganisms and making pots, the second is training in making and the third is monitoring and also evaluation. The activity was carried out by making planting media in the form of pots with gallons and used aqua bottles, then continuing with making fertilizer using stale rice, namely local microorganisms (MOL), then continuing with planting vegetables.